Evaluating the Implementation of the Right to Information Act: An Analytical Perspective on its Administrative Impact - Harshit Singh; Praveen Kumar Chauhan (Educational Administration: Theory and Practice, 2023)
This research paper provides a detailed analytical study on the implementation of the Right to Information (RTI) Act in India and evaluates its multifaceted impact on public administration. The RTI Act, introduced as a tool to promote transparency and accountability in governance, has triggered significant changes in the way government institutions interact with citizens. The study explores key aspects such as the responsiveness of public authorities, the efficiency of information dissemination, institutional reforms, and administrative challenges encountered during the process. A mixed-method approach was adopted to ensure comprehensive coverage-quantitative data from central and state information commissions was analyzed to track filing and disposal patterns, while qualitative insights were gathered through interviews with Public Information Officers (PIOs), civil society members, and RTI applicants. Furthermore, a structured survey conducted with 200 RTI users provided first-hand citizen feedback on service quality. The paper concludes that while the RTI Act has enhanced administrative transparency and improved civic engagement, several implementation bottlenecks-such as bureaucratic inertia, delays in response, and procedural ambiguity-continue to hinder its optimal impact. The study offers actionable recommendations to strengthen the RTI regime and foster a more open, accountable administrative ecosystem.